REGULATION OF SERUM CORTISOL BY SOMATOSTATIN: EVIDENCE OFNEUROENDOCRINECONTROLOFADRENALGLANDIN AMPHIBIA - NEHAR, SHAMSHUN (The Bioscan, 2007)
The role of somatostatin in plasma cortisol level in Rana tigrina (amphibia,anura) has been investigated. An inhibitory impact on both, intact (16.32%) as well as pharmacologically annuled frogs(23.27%) has been recorded. It is concluded that in both the conditions, it act as a preventive agent to counteract any excess secretion of cortisol due to the failure of classical regulatory mechanism.